If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(u-9)=5u-10
We move all terms to the left:
-2(u-9)-(5u-10)=0
We multiply parentheses
-2u-(5u-10)+18=0
We get rid of parentheses
-2u-5u+10+18=0
We add all the numbers together, and all the variables
-7u+28=0
We move all terms containing u to the left, all other terms to the right
-7u=-28
u=-28/-7
u=+4
| 2/3(3x+46)=x+85 | | 3=-q–64q=-6q=6 | | 3x+46=1/3(x+85) | | 5(3k+2)+4k=14k-12+7k-2-2k* | | z/2-1=4 | | x^2+12.5x+156.25=0 | | 3(11+a)=9 | | 2+7X3x=18 | | 4(x–5)+2x=9x–2(4+2x) | | 17=3-2r+6 | | 2/3+2r=-18/15 | | 9=9q-10q | | -v+33=0 | | 5x2+14x=3 | | (3-x/4)-3=-1 | | q/6-8=-6 | | 13=4y-3 | | 12+2x−=9x+6 | | 3(x-4)=X+7 | | 0.2r+0.75=0.5r+0.3 | | 3-x/4-3=-1 | | 4*1/4=n | | 7x/6-21=0 | | 2x+8=2(x+4) | | 102+-7x=85 | | 2(2x-7)=7(7x-2 | | -5b-12=13 | | 3+8n=6n+3(2+n) | | 10n/7-4=6 | | n+0=2/3 | | 2x+35=x+45 | | 7−5+3x−1=7-5+3x-1=x+x+ |